Effect of obstructive sleep apnoea on diabetic retinopathy and maculopathy: a systematic review and meta‐analysis. Issue 2 (4th July 2015) - Leong, W. B.; Jadhakhan, F.; Taheri, S.; Chen, Y. F.; Adab, P.; Thomas, G. N.
Abstract: Aims: To summarize the association between obstructive sleep apnoea and diabetic retinopathy and diabetic maculopathy, and to examine the effects of oxygen desaturation index, mean and minimum oxygen saturation and time spent with < 90% oxygen saturation on diabetic retinopathy and diabetic maculopathy. Methods: A systematic search was performed for papers published from inception to January 2014 in MEDLINE, EMBASE and the Cochrane Database of Systematic Reviews using indexed terms and free text. Additional searches were carried out for grey literature. Two authors conducted the study selection and quality assessment. Data extraction was performed by the main author and checked by the other authors. Results: One cohort study and 15 cross‐sectional studies were included for narrative synthesis and three for meta‐analyses. There was no convincing evidence that obstructive sleep apnoea was associated with diabetic retinopathy, although some evidence suggested that obstructive sleep apnoea was associated with greater severity of diabetic retinopathy and advanced diabetic retinopathy in people with Type 2 diabetes. Only six studies examined the impact of obstructive sleep apnoea on diabetic maculopathy and our narrative review suggests there is an association in Type 2 diabetes. Oxygen desaturation index, mean oxygen saturation or time spent with < 90% oxygen saturation were not associated with diabetic retinopathy, and insufficient evidence was available to draw conclusions on their effects on diabetic maculopathy; however, there was evidence from both narrative synthesis and meta‐analysis that minimum oxygen saturation had an impact on diabetic retinopathy (pooled odds ratio 0.91, 95% CI 0.87–0.95; I 2 = 0%). Conclusions: There is a need for large cohort studies with long‐term follow‐up data to examine the long‐term effects of obstructive sleep apnoea and other sleep variables on advanced retinal disease in diabetes. What's new?: Obstructive sleep apnoea (OSA), accompanied by hypoxaemia, is common amongst patients with type 2 diabetes mellitus. Recently, it has been proposed that OSA and hypoxemia are associated with retinal disease in diabetes. A systematic review was conducted to examine this association. The systematic review highlighted several methodological pitfalls in previous studies, but identified that minimum nocturnal oxygen saturation was associated with diabetic retinopathy. Thus, there is a need to consider hypoxemia as an important contributor to retinal disease in diabetes.